(untitled) (Ictus, 2022)
Introduction: Intracranial aneurysms represent an abnormal dilatation on the arterial wall of the cerebral vessels. There is a controversy about the best treatment for ruptured aneurysms located at the middle cerebral artery bifurcation. Case Report: 63-year-old male, presented with left facial paralysis and ipsilateral paresthesia associated with right palpebral ptosis. CT Angiography revealed bleeding in the subarachnoid space, Fisher grade I and the presence of a ruptured, wide neck saccular aneurysm in right middle cerebral artery. Given the size and shape of this wide neck aneurysm (5 mm neck dimension, 7.4 mm height/neck aspect radio and dome/neck radio of 7.43mm.) added to its location, we considered the usage of Woven Endobridge device for endovascular embolization. The device was suitable because of its preferred wide-neck indication (mayor/igual 4mm). Conclusions. Mexico´s experience with intracranial WEB device remains scarce, therefore, pointing out different therapeutic options but neurosurgical clipping highly benefits patients in our country.